Negative-sequence current capability in low-capacitance cascaded H-bridge static compensators with optimal third-harmonic circulating current injection - Ramos, Ezequiel Rodriguez (2023)
The cascaded H-bridge (CHB) low-capacitance static compensator (LC-StatCom) has a limited negative-sequence current injection capability compared to a conventional CHB StatCom, due to the comparatively larger oscillations on the capacitor voltages. Placing limits on the ability to provide negative-sequence current to the grid for a given capacitor size is required to prevent overmodulation. This article shows that these limits can be maximized by injecting an optimal third-harmonic circulating current. The effects of injecting the third-harmonic current on the capacitor voltages, both in balanced and unbalanced grid voltage conditions, are analyzed. Specifically, the procedure allows the knowledge of the potential capability of the LC-StatCom when injecting negative-sequence currents. The procedure is based on a linear programming approach. Although the procedure is applicable to any CHB StatCom, regardless of the submodule capacitor size, it is particularly important in LC-StatComs. To corroborate the proposed analysis, simulation and experimental results under balanced and unbalanced grid voltage conditions are presented.